Cancer Patients Have a Higher Risk Regarding COVID-19-and Vice Versa? - Franz Geisslinger; Angelika M. Vollmar; Karin Bartel (MDPI AG, 2020)
The world is currently suffering from a pandemic which has claimed the lives of over 230,000 people to date. The responsible virus is called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and causes the coronavirus disease 2019 (COVID-19), which is mainly characterized by fever, cough and shortness of breath. In severe cases, the disease can lead to respiratory distress syndrome and septic shock, which are mostly fatal for the patient. The severity of disease progression was hypothesized to be related to an overshooting immune response and was correlated with age and comorbidities, including cancer. A lot of research has lately been focused on the pathogenesis and acute consequences of COVID-19. However, the possibility of long-term consequences caused by viral infections which has been shown for other viruses are not to be neglected. In this regard, this opinion discusses the interplay of SARS-CoV-2 infection and cancer with special focus on the inflammatory immune response and tissue damage caused by infection. We summarize the available literature on COVID-19 suggesting an increased risk for severe disease progression in cancer patients, and we discuss the possibility that SARS-CoV-2 could contribute to cancer development. We offer lines of thought to provide ideas for urgently needed studies on the potential long-term effects of SARS-CoV-2 infection.